A platform for change?. (June 2015) - Williams, Val; Ponting, Lisa; Ford, Kerrie; Williams, Val; Tarleton, Beth
<x xml:space="preserve">Abstract</x> Accessible summary The governments in the UK want people with learning disabilities to have a voice about what happens in their own life and also in policy. One way of doing this is through research. This paper looks at two inclusive research projects, which were about people using direct payments and personal assistants. The projects both employed people with learning disabilities. Each of these projects made a training pack from the research, so that they would help people with learning disabilities and their supporters. They also had some effects in ways that were not planned, because the government wanted to learn from them about inclusive research. All research seems to have most effect when there are many voices seeking change, including those of policy makers themselves. Inclusive research is a way of achieving 'choice and control'. But just like with direct payments and personal budgets, the best way in these projects was to have good support from other people who will listen to you, and help you decide things for yourself. Summary Participation, voice and control have long been central concerns in the research at Norah Fry. This paper focuses on inclusive research relating to choice and control, as experienced by people with learning disabilities who use personal budgets and direct payments, and aims to question how the process of inclusive research can be linked to wider outcomes. The paper gives a brief overview of two studies carried out by Norah Fry Research Centre, which were in partnership with self‐advocacy groups and employed people with learning disabilities, between 1999 and 2007. Both in research and in everyday life, we question individual notions of 'choice and control', showing how relational autonomy was at the heart, both of the process of the inclusive research and also of the outcomes and findings. However, all social research seems to have greatest impact when there is a 'bandwagon effect' of policy and practice initiatives. The discussion considers how the impact of inclusive research designs can be at policy, practice and 'direct' user level and is often achieved by people with learning disabilities having a voice at the dissemination stage.